2014
DOI: 10.1002/pa.1558
|View full text |Cite
|
Sign up to set email alerts
|

State environmental regulators: perspectives about trust with their regulatory counterparts

Abstract: Although numerous studies explore the regulatory enforcement styles of regulators and the regulated community's compliance motivations, existing research does not provide adequate insight into regulatory interactions themselves. We use data from a nationwide survey of more than 1200 state environmental regulators to empirically assess the role of trust in regulatory interactions. We find statistical support of trust in these regulatory interactions and find that trust appears to be a function of cooperative be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Pautz (2009) found that most interactions between environmental inspectors and regulatory officials were characterized by trust between the parties. Pautz and Rinfret (2016) found that trust in regulatory interactions leads to cooperative behavior, information sharing, and respect. Rorie et al (2015) found that trust plays an important role for both regulated community and regulators in determining whether a sanction will be applied.…”
Section: Regulation Trust and Front-line Workersmentioning
confidence: 99%
“…Pautz (2009) found that most interactions between environmental inspectors and regulatory officials were characterized by trust between the parties. Pautz and Rinfret (2016) found that trust in regulatory interactions leads to cooperative behavior, information sharing, and respect. Rorie et al (2015) found that trust plays an important role for both regulated community and regulators in determining whether a sanction will be applied.…”
Section: Regulation Trust and Front-line Workersmentioning
confidence: 99%
“…The five characteristics described above can interact with and reinforce one another (Fig 2 ). For example, mutual clarity about each party's needs and constraints-including what outcomes they are working toward, what responsibilities they have, and what risks they face [47,[156][157][158]-can develop over time through repeated interactions [21,56,159] (continuity) and help to foster trust in the other party's motives [160], demonstrate where they are in alignment, identify where bounded flexibility may be both possible and beneficial, and highlight where PLOS WATER capacity building is needed. Sustained interactions can help to build trust and legitimacy [161].…”
Section: Synergies and Interdependencies Between The Five Characteris...mentioning
confidence: 99%
“…Subsequent theoretical developments have focused on the contexts of tax, environmental, and financial regulations, which are encompassing and permeate a variety of industries. A common element across the literature, however, is the emphasis on information asymmetry, whereby authorities have limited access to information about firms’ activities and operations (this is also referred to as an information gap; Baron and Myerson [], Sappington [], Besanko and Sappington [], Pautz and Rinfret []). The fundamental problem for authorities is that monitoring is costly, as they have limited capacity and resources to process technical and extensive information in order to effectively assess whether firms are failing to comply with regulations.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Across diverse regulatory settings, authorities request proprietary information from firms as part of their monitoring and supervision strategies. This is particularly relevant in contexts in which there is a significant information gap between the firm and the authority (Besanko and Sappington [], Pautz and Rinfret []). In the contexts of tax, customs, financial, or environmental regulations, for instance, firms are commonly requested to complete and submit mandatory self‐assessments in which they report sensitive information.…”
Section: Introductionmentioning
confidence: 99%